Reactivity of disulfide bonds is markedly affected by structure and environment: implications for protein modification and stability - Karimi, Maryam; Ignasiak, Marta T.; Chan, Bun; Croft, Anna K.; Radom, Leo; Schiesser, Carl H.; Pattison, David I.; Davies, Michael J. (Nature Publishing Group, 2016)
Disulfide bonds play a key role in stabilizing protein structures, with disruption strongly associated with loss of protein function and activity. Previous data have suggested that disulfides show only modest reactivity with oxidants. In the current study, we report kinetic data indicating that selected disulfides react extremely rapidly, with a variation of 104 in rate constants. Five-membered ring disulfides are particularly reactive compared with acyclic (linear) disulfides or six-membered rings. Particular disulfides in proteins also show enhanced reactivity. This variation occurs with multiple oxidants and is shown to arise from favorable electrostatic stabilization of the incipient positive charge on the sulfur reaction center by remote groups, or by the neighboring sulfur for conformations in which the orbitals are suitably aligned. Controlling these factors should allow the design of efficient scavengers and highstability proteins. These data are consistent with selective oxidative damage to particular disulfides, including those in some proteins.